2017
DOI: 10.1186/s13643-017-0520-9
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a comprehensive approach to Aboriginal tobacco control to maintain the decline in smoking: an overview of reviews among Indigenous peoples

Abstract: BackgroundTobacco smoking is a leading cause of disease and premature mortality among Aboriginal and Torres Strait Islander (Indigenous) Australians. While the daily smoking prevalence among Indigenous Australians has declined significantly from 49% in 2001, it remains about three times higher than that of non-Indigenous Australians (39 and 14%, respectively, for age ≥15 years in 2014–15). This overview of systematic reviews aimed to synthesise evidence about reducing tobacco consumption among Indigenous peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 53 publications
2
55
0
Order By: Relevance
“…5,21 It is not possible to determine if any individual component has been more effective than others, but measures that are Indigenous-led and culturally tailored are identified as particularly important. 21,23 A greater understanding of what works for young people of different ages is needed to design programs that continue to prevent smoking throughout adolescence and into adulthood. 23 Our results may indicate a trend towards delayed smoking initiation, with the largest increase in never smoking since 2002 among 18-19-year-olds and more moderate changes among 20-24-year-olds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,21 It is not possible to determine if any individual component has been more effective than others, but measures that are Indigenous-led and culturally tailored are identified as particularly important. 21,23 A greater understanding of what works for young people of different ages is needed to design programs that continue to prevent smoking throughout adolescence and into adulthood. 23 Our results may indicate a trend towards delayed smoking initiation, with the largest increase in never smoking since 2002 among 18-19-year-olds and more moderate changes among 20-24-year-olds.…”
Section: Discussionmentioning
confidence: 99%
“…21,23 A greater understanding of what works for young people of different ages is needed to design programs that continue to prevent smoking throughout adolescence and into adulthood. 23 Our results may indicate a trend towards delayed smoking initiation, with the largest increase in never smoking since 2002 among 18-19-year-olds and more moderate changes among 20-24-year-olds. As shown previously for both Indigenous and non-Indigenous people 5 , we found that the majority of Indigenous adolescents and young adults who have ever smoked regularly started smoking before age 18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore hit a dilemma: what cessation support should even be offered? Systematic reviews on Aboriginal tobacco control have concluded that there is limited evidence of effective programs for Aboriginal and Torres Strait Islander people in general as well as during pregnancy …”
Section: The Problem With Reductionmentioning
confidence: 99%
“…Little research considers the appropriateness and transferability of initiatives elsewhere to Aboriginal and Torres Strait Islander contexts (Van der Sterren et al 2016), while there is a need for Indigenous-specific research regarding: the impact of pricing measures; interventions to reduce tobacco use among adolescents and pregnant women; the effects of the introduction of smoking bans in prisons; and linguistically diverse Indigenous people. There is also a need for Indigenous-specific evidence regarding interventions using social media and mobile applications, electronic cigarettes, and how to protect communities from industry interference (Chamberlain et al 2017). Robertson et al's 2015 systematic review of trends in Indigenous Australian tobacco research from 2004 to 2013 found that, despite a surge in research output in 2008 relating to Indigenous tobacco control, there were still few intervention studies available to guide future efforts.…”
Section: Tobacco Interventions In Indigenous Communitiesmentioning
confidence: 99%